Development of Islamic Education Teaching Materials based on Local Culture to Improve the Honest Character of Elementary School Students - Aziza Aryati; Nurul Fadilah; Wifqo Arova Syams (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: Development of Islamic Education Teaching Materials based on Local Culture to Improve Honest Character in Elementary School StudentsObjective: This study aims to develop local culture-based Islamic religious education teaching materials to improve the honest character of elementary school students. Method: This type of research uses a research and development (R&D) approach, which consists of needs analysis, teaching material design, limited trials, and evaluation. Data were collected through observation, interviews with teachers and students, and analysis of related documents. Results: The developed teaching materials successfully link local cultural values with Islamic teachings, such as through folklore and cultural symbols relevant to the concept of honesty in Islam. Conclusion: Developing local culture-based teaching materials can be an effective strategy in Islamic religious education to strengthen the formation of honest character in elementary school students. Contribution: The research contributes as a model of teaching materials based on local culture that can be applied in elementary schools and provides new insights into integrating local culture in Islamic religious education for student character building.INDONESIAN: Pengembangan Bahan Ajar Pendidikan Agama Islam Berbasis Budaya Lokal untuk Meningkatkan Karakter Jujur Siswa Sekolah DasarTujuan: Penelitian ini bertujuan untuk mengembangkan bahan ajar pendidikan agama Islam berbasis budaya lokal yang dapat meningkatkan karakter jujur siswa sekolah dasar. Metode: Jenis penelitian menggunakan pendekatan penelitian dan pengembangan (R&D), yang terdiri dari tahap analisis kebutuhan, desain bahan ajar, uji coba terbatas, dan evaluasi. Data dikumpulkan melalui observasi, wawancara dengan guru dan siswa, serta analisis dokumen terkait. Hasil: Bahan ajar yang dikembangkan berhasil mengaitkan nilai-nilai budaya lokal dengan ajaran Islam, seperti melalui cerita rakyat dan simbol budaya yang relevan dengan konsep kejujuran dalam agama Islam. Kesimpulan: Pengembangan bahan ajar berbasis budaya lokal dapat menjadi strategi yang efektif dalam pendidikan agama Islam untuk memperkuat pembentukan karakter jujur pada siswa sekolah dasar. Kontribusi: Penelitian berkontribusi sebagai model bahan ajar yang berbasis budaya lokal yang dapat diterapkan di sekolah dasar, serta memberikan wawasan baru tentang pengintegrasian budaya lokal dalam pendidikan agama Islam untuk pembentukan karakter siswa.